THE EFFECTIVENESS OF USING COOPERATIVE LEARNING MODEL TYPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) ON STUDENT LEARNING OUTCOMES - Asmiyati Megah Sundari; Abdul Taram (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Mathematics learning in class XI SMK N 1 Sewon is still centered on teachers. Students assume that mathematics is a complicated subject that resulted in the students' mathematics learning outcome. Learning using Student Team Achievement Division (STAD) type cooperative learning model is expected to improve students' mathematics learning outcomes. This research is aimed to find out whether or not the difference of mathematics learning result of the students is taught by using STAD type cooperative learning model and by using direct learning model, and which is better learning model to student learning achievement, STAD type cooperative learning model or model direct learning. This study's population were students of Class XI Hospitality Accommodation Program (AP) State Vocational High School (SMK N) 1 Sewon consisting of three classes. In contrast, the sample in this study, there are two classes determined by random sampling. The research sample is class XI (AP-1 ) as an experiment class with STAD type cooperative learning model, and class XI (AP-2 ) as a control class with a direct learning model. This research instrument is the test result of mathematics learning and analyzed using the validity test, distinguishing power, and reliability. Then, the data analysis uses a two-t-test and one-party test. The first hypothesis test analysis is two t-test on the students' mathematics learning results. A significance level of 5% and degrees of freedom 53 obtained tcount = 4.560, and ttable = 2.00584 then tcount> ttable. Hence, there is a significant difference between the learning results in mathematics of students taught by using STAD type cooperative learning model and by using direct learning model, and on second hypothesis test that is t-test one side with 5% significance level and degrees of freedom 53 obtained tcount= 4,560, and ttable = 1,67416, then tcount > ttable so that model of cooperative learning type STAD better than direct learning model to result of student learning of mathematics.